Multi-robot semantic mapping based on deep learning framework - Zhao, Chunyang (Nanyang Technological University, 2020)
In this work, we mathematically model the collaborative semantic perception problem with derive its probability decomposition, based on which we propose a novel incremental hierarchical collaborative probabilistic semantic mapping framework where a multi-modal sensor data fusion method is utilized to incorporate information of sensors, a Bayesian based update scheme is employed to update the current state with prior knowledge and current observations, an Expectation-Maximization approach is exploited to infer the hidden data association between local maps.